Kinetics and Mechanism of the Oxidation of Lactic Acid and Mandelic Acid by Pyridinium Chlorochromate in Aqueous Acidic Medium - Sapana Jain; B. L. Hiran; C. V. Bhatt (E-Journal of Chemistry)
Pyridinium chlorochromate (PCC) act as two electron oxidant in kinetic studies of the oxidation of lactic and mandelic acid in acidic medium. The influence of several factors such as acidity, salts, solvent composition and temperature on the reaction rate has been studied. The reaction shows first order dependence with respect to [PCC] and [H+]. The various thermodynamic parameters have been evaluated. Products as oxoacids and absence of free radical were confirmed. Suitable reaction mechanism has been proposed.